2019
DOI: 10.1177/1553350619853099
|View full text |Cite
|
Sign up to set email alerts
|

Video Technologies for Recording Open Surgery: A Systematic Review

Abstract: Video recording of surgical procedures is an important tool for surgical education, performance enhancement, and error analysis. Technology for video recording open surgery, however, is limited. The objective of this article is to provide an overview of the available literature regarding the various technologies used for intraoperative video recording of open surgery. A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…), selected initial propositions based on personal experience, video guidelines of major journals, and a literature review. 3,5,10,[12][13][14][15][17][18][19][20][21][22][23] A Delphi questionnaire was created, and the propositions were reviewed online by the entire consensus committee in three rounds. Blinded feedback was shared among respondents between each round, and the respondents were able to suggest new propositions at the end of round 1.…”
Section: Methodsmentioning
confidence: 99%
“…), selected initial propositions based on personal experience, video guidelines of major journals, and a literature review. 3,5,10,[12][13][14][15][17][18][19][20][21][22][23] A Delphi questionnaire was created, and the propositions were reviewed online by the entire consensus committee in three rounds. Blinded feedback was shared among respondents between each round, and the respondents were able to suggest new propositions at the end of round 1.…”
Section: Methodsmentioning
confidence: 99%
“…Livestreaming of surgical procedures has previously been described in a variety of surgical fields. 1 , 8 Recently, remote surgical training has become a relevant solution to address the surgical training gaps that medical students and residents may have experienced as a result of the COVID-19 pandemic. 4 Articles have expressed concerns about the safety of livestreaming surgeries, 3 , 5 - 7 but studies have shown that patient safety and outcomes are not compromised.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no reports in the literature that delineate steps in setting up a portable live-surgery streaming system in a Health Insurance Portability and Accountability Act (HIPAA)–compliant manner. 8 This involves the surgeon donning a headgear to wirelessly transmit the camera’s video feed to a computer without being tethered to a machine or to the institution’s infrastructure and audiovisual cost center. The livestream received on the computer can then be shared using a HIPAA-compliant teleconferencing platform.…”
Section: Introductionmentioning
confidence: 99%
“…At present, video cameras remain in use to capture medical procedures for the purposes of quality improvement, training, and research [1,2]. A recent systematic review on video recording open surgeries included 110 articles that discussed camera use to capture open surgery with miniature cameras, such as GoPro (GoPro, Inc.) and GoogleGlass (Alphabet, Inc) [3]. Outside of surgical specialties, video recordings are widely used to correlate clinical findings with electroencephalogram findings in patients with suspected seizures [4-6] and may also be used to study team dynamics and technical skills in emergency cardiopulmonary resuscitation [7].…”
Section: Introductionmentioning
confidence: 99%